Role of Advance Nuclear Medicine Imaging Techniques in Preclinical Drug Development and Three R's in Animal Research (Journal of Laboratory Animal Science, 2024)
Preclinical models have played a fundamental role in understanding the pharmacokinetics and biodistribution of novel  drugs and radiopharmaceuticals prior to its clinical testing. Application of radiotracers and Nuclear Imaging Techniques  have the potential of real time tracking of radiotracer molecules in a non-invasive manner. The three R’s principles are now  a worldwide commitment for laboratory animals. Hence, we have carried out PET/CT and scintigraphy imaging technique  for monitoring and exploring the in vivo pharmacokinetic profiles of novel drugs in the lung, tumor site, stomach as well as their systemic retention in animals. The present work includes different case studies viz. Evaluation and gastric retention  of radiolabeled metformin floating tablet  in rabbits by gamma scintigraphy; and Normal biodistribution of radiolabeled etoposide-nano-formulation in New Zealand White rabbit and evaluation of anticancer activity in C57BL/6 mice as a lung  metastatic melanoma tumor model. Results showed that the gastric retention of radiolabeled metformin floating tablet was observed to be 50% in the rabbit stomach up to 6h post administration and radiolabeled etoposide-nano-formulation  showed 97% of lung uptake in normal rabbit at 1h and significant regression in the number of lung metastasis sites in mice tumor model. Successful drug delivery information can be obtained by in vivo monitoring which enables acquiring  statistically significant data from a limited number of animals by the advance imaging modalities. These techniques have an added advantage to provide the 'Reduction' principle in laboratory animals and also boost the research and development  for new drugs and radiopharmaceuticals.
Keywords: Laboratory animals; Drug delivery; Radiotracer; 3 R's; Nuclear Medicine Imaging